2018
DOI: 10.1111/jbi.13398
|View full text |Cite
|
Sign up to set email alerts
|

A trait‐based approach reveals the importance of biotic filter for elevational herb richness pattern

Abstract: Aim To evaluate how a biotic filter (overstorey cover [OC]) shapes an elevational herb richness pattern and to test whether intermediate elevations represent more suitable habitats for herb species due to the minimal biotic and moderate abiotic filtering that occured there. Location Dongling Mountain, China. Taxon Herbs. Methods We sampled herb richness along a 1,000‐m vertical transect (OC and elevation covary) and four horizontal transects (across the OC gradient with no change in elevation). Functional trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…This can be explained by intermediate disturbance hypothesis or other urban-related disturbances, similar to previous studies in Chinese cities [14,92,93]. In addition, the majority of the annual herbs we recorded are ruderal species, which evolve with different survival strategies to diverse habitats and multiple disturbances [94][95][96]. Exotic plant species richness exhibited a slightly negative quadratic relationship with urbanization degree, which means the introduction of an exotic plant could increase the total plant species richness associated with the urbanization process, which was also demonstrated by previous studies [75,97].…”
Section: The Impacts Of Urbanization On Plant Diversitysupporting
confidence: 83%
“…This can be explained by intermediate disturbance hypothesis or other urban-related disturbances, similar to previous studies in Chinese cities [14,92,93]. In addition, the majority of the annual herbs we recorded are ruderal species, which evolve with different survival strategies to diverse habitats and multiple disturbances [94][95][96]. Exotic plant species richness exhibited a slightly negative quadratic relationship with urbanization degree, which means the introduction of an exotic plant could increase the total plant species richness associated with the urbanization process, which was also demonstrated by previous studies [75,97].…”
Section: The Impacts Of Urbanization On Plant Diversitysupporting
confidence: 83%
“…Here, we found that overstorey functional diversity also had a negative effect on the functional diversity of understorey communities. This result suggests that overstorey trees could act as a biotic filter that structures understorey communities (Jiang et al, ). Meanwhile, canopy cover could be related to the composition and diversity of ground‐layer plant communities, because light conditions are generally thought to be an important resource in the forest understorey (Shigyo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that overstorey trees could act as a biotic filter that structures understorey communities (Jiang et al, 2018).…”
Section: The Relative Importance Of Environmental Variablesmentioning
confidence: 96%
See 1 more Smart Citation
“…Elevation is a key factor that determines the patterns of plant diversity in mountainous areas (Jiang et al, 2018;Körner, 2007;Lee et al, 2013;Lee & La Roi, 1979). The patterns of plant diversity are often explained by several hypotheses for elevational diversity gradient such as the mass effect, mid-domain effect, and Rapoport's elevational rule.…”
Section: Introductionmentioning
confidence: 99%